PEMETAAN PERCEPATAN GETARAN TANAH MAKSIMUM MENGGUNAKAN PENDEKATAN PROBABILISTIC SEISMIC HAZARD ANALYSIS (PSHA) DI KABUPATEN KEPAHIANG PROVINSI BENGKULU - Hadi, Arif Ismul; Brotopuspito, Kirbani Sri (BERKALA FISIKA, 2015)
This study aims to analyze and map the peak ground acceleration using the approach of Probabilistic Seismic Hazard Analysis (PSHA) in the area. Earthquake catalog data obtained from BMKG, ISC and USGS began in 1914 until 2014. Declustering process using ZMAP ver.6 software. Identification and modeling of the seismic source uses three models of seismic sources: (1) to subduction earthquake source, (2) the source of the earthquake fault and (3) the source of the quake background. Parameters a-value and b-value is obtained by the Gutenberg-Richter recurrence law and maximum likelihood method, whereas the determination of the attenuation function and logic tree refers to the Revision Team of Indonesia Earthquake 2010. Peak ground acceleration values obtained using USGS-PSHA-07 software. The results showed that the value of the peak ground acceleration in the Kepahiang District for probability exceeded 10% and 2% in the 50 year design life of the building is 0.15 – 0.8 g and 0.25 – 1.3 g. Areas that are the red zone is the Ujan Mas Sub-district, Kepahiang Sub-district, Tebat Karai Sub-district, Seberang Musi Sub-district and Bermani Ilir Sub-district, while the regions are relatively safe from the red zone is the Merigi Sub-district, Kabawetan Sub-district and Muara Kemumu Sub-district. Red zone is an area adjacent to the Sumatran Fault of Musi Segment. Keywords: peak ground acceleration, PSHA, red zone and Sumatran Fault of Musi Segment.